Low barrier buprenorphine treatment for persons experiencing homelessness and injecting heroin in San Francisco - Carter, Jamie (Addict Sci Clin Pract, 2019)
BACKGROUND: Opioid overdose is a leading cause of death in persons experiencing homelessness (PEH), despite effective medications for opioid use disorder (OUD). In 2016, the San Francisco Street Medicine Team piloted a low barrier buprenorphine program with the primary goal of engaging and retaining PEH with OUD in care as a first step toward reducing opioid use and improving overall health. OBJECTIVE: To characterize the patients; assess treatment retention, retention on buprenorphine, and opioid use; and to describe adverse events. METHODS: Retrospective chart review of patients receiving at least one buprenorphine prescription from Street Medicine (November 2016–October 2017). We abstracted demographic, medical, substance use, prescription, and health care utilization data from medical records. We assessed retention in care at 1, 3, 6, 9 and 12 months, defined as a provider visit 1 week prior to or any time after each time point. We considered patients to be retained on buprenorphine if they had active buprenorphine prescriptions for more than 2 weeks of the month. We estimated opioid use by the percentage of patients with any opioid-negative, buprenorphine-positive urine toxicology test. We reviewed emergency department and hospital records for adverse events, including deaths and nonfatal opioid overdoses. RESULTS: Among the 95 persons eligible for analysis, mean age was 39.2, and 100% reported injecting heroin and homelessness. Medical and psychiatric comorbidities and co-occurring substance use were common. The percentages of patients retained in care at 1, 3, 6, 9 and 12 months were 63%, 53%, 44%, 38%, and 26%, respectively. The percentages of patients retained on buprenorphine at 1, 3, 6, 9 and 12 months were 37%, 27%, 27%, 26%, and 18%, respectively. Twenty-three percent of patients had at least one opioid-negative, buprenorphine-positive test result. One patient died from fentanyl overdose, and four patients presented on six occasions for non-fatal overdoses requiring naloxone. CONCLUSIONS: This program engaged and retained a subset of PEH with OUD in care and on buprenorphine over 12 months. While uninterrupted treatment and abstinence are reasonable outcomes for conventional treatment programs, intermittent treatment with buprenorphine and decreased opioid use were more common in this pilot and may confer important reductions in opioid and injection-related harms.